الانتظار في القرآن الكريم –دراسة موضوعية- - كريب يونس (University of Eloued جامعة الوادي, 2023)
هذا المقال يبحث في أسلوب الانتظار كأسلوب قرآني فعال، يخرج الله به الناس من الظلمات إلى النور . وقد تناول فيه الباحث تعريف الانتظار والألفاظ المقاربة لها مثل التربص والإرصاد وغيرهما، ثم تناول فيه الباحث تأصيل المنهج من خلال القرآن لتظهر مدى عناية القرآن به كمنهج فعال ، ثم تناول الباحث أغراض الانتظار وثمراته المتحصل عليها ليخرج البحث في صيغته الآتية . :Abstract This article examines the method of waiting as an effective Qur'anic method, through which God brings people out of darkness into light. In it, the researcher dealt with the definition of waiting and the words close to it, such as waiting, meteorology, and others, then the researcher dealt with the rooting of the method through the Qur’an to show the extent of the Qur’an’s care for it as an effective approach, then the researcher dealt with the purposes of waiting and its fruits obtained to produce the research in its following form
Keywords: لانتظار; سياقاته; أغراضه; دلالاته; منهجه; Waiting; Contexts; Purposes; Significance; Methodology